ABO BLOOD GROUPS AND SERUM LIPIDS IN PATIENTS WITH ISCHAEMIC HEART DISEASE - Akhund, Israr Ahmed; Akhund, Anwar Ali; Alvi, Irshad Ali; ullah, Hafeez; Ansari, Ahmed Kamal (Journal of Ayub Medical College Abbottabad, 1998)
To assess the association of Blood Groups with Serum Lipids in patients with ischaemic heart disease, two hundred patients were reviewed. Patients belonging to blood group A had higher mean serum cholesterol levels (p<0.01) than those belonging to Groups O, B and AB. Slightly higher than upper normal values of serum cholesterol were also seen in group A healthy control. Statistical analysis revealed that the blood group A was an independent risk factor for the development of Ischaemic heart disease.